2009
DOI: 10.1111/j.1464-410x.2009.08532.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs open prostatectomy in a laparoscopically naive centre: a matched‐pair analysis

Abstract: . All patients were operated by the same laparoscopically naive surgeons. The comparison was by matched-pair analysis. RESULTSThe baseline characteristics of the two groups were equivalent, although there was a higher percentage of patients with pT3/pT4 disease in the RRP group. As a proxy for oncological outcome, positive surgical margins were equivalent in the two groups (22% RARP vs 25% RRP, P = 0.77). The overall mean (range) surgical duration was significantly longer in RARP group, at 215 (165-450) min vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
3
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 27 publications
8
128
3
7
Order By: Relevance
“…7,8 Ahlering et al also reported that a laparoscopically naïve yet experienced open surgeon using a robotic interface successfully transferred open surgical skills to a laparoscopic environment in 8-12 cases. 3 These reports, however, were based on operations carried out by well experienced open surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Ahlering et al also reported that a laparoscopically naïve yet experienced open surgeon using a robotic interface successfully transferred open surgical skills to a laparoscopic environment in 8-12 cases. 3 These reports, however, were based on operations carried out by well experienced open surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…91,95,96 Of the non-randomised comparative studies comparing robotic, laparoscopic and open radical prostatectomy, two primary studies 99,100 and one secondary report 102 were set in the USA and one study was set in France. 101 Of the nonrandomised comparative studies comparing robotic and open radical prostatectomy, 10 primary studies 103,[108][109][110][111][112][115][116][117][118] and two secondary reports 119,120 were set in the USA, one study was set in Australia, 105 three primary studies 106,107,114 were set in Italy, one study was set in Sweden 104 and one was set in Taiwan, Province of China. 113 Of the non-randomised comparative studies comparing laparoscopic and open radical prostatectomy, seven primary studies [124][125][126]128,142,145,146 and one secondary report 147 were set in the USA, three primary studies 127,131,137 were set in Germany, three primary studies 135,136,144 were set in Japan, three primary studies 123,129,134 were set in Italy, two primary studies 122,140 were set in France and one study each was set in Austria, 139 Brazil,…”
Section: Number and Type Of Included Studiesmentioning
confidence: 99%
“…However, EBL, hospitalization time, and functional outcomes were superior with RARP. Early oncological outcome seemed to be equivalent in the two groups (Rocco et al, 2009). The drawback of RARP is the cost related to purchasing and maintaining the instruments of the robotic system.…”
Section: Prostatectomymentioning
confidence: 88%